Promoting Photocatalytic Hydrogen Evolution Activity of Graphitic Carbon Nitride with Hole‐Transfer Agents. Issue 1 (27th November 2020) - Indra, Arindam; Beltrán‐Suito, Rodrigo; Müller, Marco; Sivasankaran, Ramesh P.; Schwarze, Michael; Acharjya, Amitava; Pradhan, Bapi; Hofkens, Johan; Brückner, Angelika; Thomas, Arne; Menezes, Prashanth W.; Driess, Matthias
Abstract: Visible light‐driven photocatalytic reduction of protons to H2 is considered a promising way of solar‐to‐chemical energy conversion. Effective transfer of the photogenerated electrons and holes to the surface of the photocatalyst by minimizing their recombination is essential for achieving a high photocatalytic activity. In general, a sacrificial electron donor is used as a hole scavenger to remove photogenerated holes from the valence band for the continuation of the photocatalytic hydrogen (H2 ) evolution process. Here, for the first time, the hole‐transfer dynamics from Pt‐loaded sol−gel‐prepared graphitic carbon nitride (Pt‐sg‐CN) photocatalyst were investigated using different adsorbed hole acceptors along with a sacrificial agent (ascorbic acid). A significant increment (4.84 times) in H2 production was achieved by employing phenothiazine (PTZ) as the hole acceptor with continuous H2 production for 3 days. A detailed charge‐transfer dynamic of the photocatalytic process in the presence of the hole acceptors was examined by time‐resolved photoluminescence and in situ electron paramagnetic resonance studies. Abstract : Holes to achieve goals : Efficient separation and transfer of holes from the graphitic carbon nitride to enhance the photocatalytic hydrogen evolution is achieved using hole‐transfer agents. A significant increment (4.84 times) in H2 production is achieved by employing phenothiazine as the hole acceptor with continuous H2 production for 3 days.